Treatment with vasoactive drugs and outcomes in surgical critically ill patients: The results from the THAI-SICU study - Thawitsri T. (2017)
© 2016, Medical Association of Thailand. All rights reserved. Objective: The purpose of this study is to assess the impact of the use of vasoactive drugs on morbidity and mortality in surgical critically ill patients. Material and Method: We conducted a multi-center prospective observational study in Thai university-based surgical intensive care units (SICU) over a 22-month period. Patient data were recorded by case record form in 3 main phases: admission, daily and discharge. Data collection included patient characteristics, pattern of vasoactive drugs use, and outcomes. Results: Nine university-based SICU comprising 4,652 patients were included in the study. The vasopressor exposed patient group had 1,155 patients (24.8%). Either vasopressor or inotrope exposed group demonstrated significantly higher ICU mortality, 28-day mortality and new arrhythmia than the non-exposed group (p < 0.001). In multivariable analysis, norepinephrine or epinephrine significantly increased risks of all unfavorable outcomes while dopamine significantly increased only new arrhythmia (OR 1.44; 95% CI 1.02-2.02, p = 0.036) in vasopressor-exposed patients. Epinephrine had the highest risk of all unfavorable outcomes with an OR 3.17; 95% CI 2.10-4.78, (p < 0.001) for ICU mortality, OR 2.62; 95% CI 1.73-3.97, (p < 0.001) for 28-day mortality, and OR of 1.77; 95% CI 1.13-2.75, (p = 0.012) for new arrhythmia. Neither dobutamine nor milrinone showed any significant results in inotrope exposed patients. Conclusion: Vasoactive drug exposed patient groups had significantly higher incidence of new arrhythmia, ICU mortality, and 28-day mortality. Epinephrine exposure was associated with the highest risk of unfavorable outcomes. Further information from well-designed studies is needed to justify the most appropriate use of vasoactive drugs.